2009
DOI: 10.1007/s00227-009-1182-5
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and demographic history of Atherina presbyter (Pisces: Atherinidae) in the North-eastern Atlantic based on mitochondrial DNA

Abstract: A fragment of the mitochondrial control region was used to assess phylogeographic patterns and historical demography of the sand-smelt Atherina presbyter in the North-eastern Atlantic, covering its geographical range. A striking result is the highly marked diVerentiation between the Canary Islands population and western European ones. A genetic structure among European populations of A. presbyter was revealed, with a pattern of isolation-by-distance or a gradient eVect at a scale of hundreds kilometres, an unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 60 publications
(69 reference statements)
2
27
0
Order By: Relevance
“…), favouring local spawning and larval retention, generating population structure. The apparent absence of such structuring within the Iberian Peninsula, in contrast, may result from corkwing wrasse larvae in this region being exposed to stronger currents and higher dispersal, leading to higher gene flow, as observed in other species in that region [13], [51], [52].…”
Section: Discussionmentioning
confidence: 86%
“…), favouring local spawning and larval retention, generating population structure. The apparent absence of such structuring within the Iberian Peninsula, in contrast, may result from corkwing wrasse larvae in this region being exposed to stronger currents and higher dispersal, leading to higher gene flow, as observed in other species in that region [13], [51], [52].…”
Section: Discussionmentioning
confidence: 86%
“…This is particularly true for haddock, pollock, and allis shad where the few molecular marker studies have indicated weak population structure among stocks, which was effectively erased during the LGM (see Jamieson andBirley, 1989 andReiss et al 2009 for haddock;Charrier et al, 2006 for pollock;and Alexandino and Boisneau, 2000 for shad). For some species, the population age estimated from molecular markers may be inexplicably older than the known length of habitat occupation since the LGM (Francisco et al, 2009). Fish of low dispersal ability are valuable tracers of glacial refugia, and the sand goby (Pomatoschistus minutus) is one such model marine species whose present population structure is a legacy of range constrictions during the glacial period (Gysels et al, The red boxes present the possible marine refugia reviewed by Maggs et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…This holds even for organisms that seem to have been able to invade the North Sea after the last glaciation (e.g. A. presbyter in Francisco et al, 2009; S. sprattus in Debes et al, 2008). This is not a generalised result and past expansion associated with the LGM has also been found in some marine organisms (e.g.…”
Section: The Complexity and Depth Of The Genealogiesmentioning
confidence: 97%
“…Finally, the values of N 0 are well above zero, indicating that the expansions began from a population that was not subjected to a drastic bottleneck. Several studies on European coastal organisms also showed past expansion events clearly older than the LGM: A. presbyter (Francisco et al, 2009), Pomatoschistus minutus (Larmuseau et al, 2009), Fucus serratus (Hoarau et al, 2007), Pollicipes pollicipes (Campo et al, 2010), etc. This holds even for organisms that seem to have been able to invade the North Sea after the last glaciation (e.g.…”
Section: The Complexity and Depth Of The Genealogiesmentioning
confidence: 98%
See 1 more Smart Citation